EFEKTIFITAS PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN PENDEKATAN STUDENT ACTIVE LEARNING DI JURUSAN MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UIN SYARIF HIDAYATULLAH JAKARTA - Syihaabul Hudaa (BAHASTRA, 2018)
Indonesian language is a must subject that all of the university student should be taken in term of their final task, which is scientific work, named skripsi. The lecturer of Indonesian language has concern in term of the lack of written ability that the university students nowadays have. The researcher’s effort in the affectivity of Indonesian language learning by using student active learning method, which is the emphasize of student activity in the classroom. This method requires student to interact in the learning process. Beside that, student should also have criticism to the problem that might be happen in the classroom’s learning process. The purpose of writing this article is to examine the learning of Indonesian conducted in the Management class in UIN Syarif Hidayatullah by using student active learning. Through the method of student active learning that has been examined by the researcher in the Management classroom A and B in Economic and Business Faculty of UIN Syarif Hidayatullah Jakarta, the researcher has the satisfactory result in the Management classroom A, and the unsatisfactory result in the Management classroom B. The average score of mid-semester test of the Management classroom A is 83,14 (A), The average score of mid-semester test of the Management classroom B is 72 (B). The average score of final-semester test of the Management classroom A is 80,4 (A) The average score of final-semester test of the Management classroom B is 78,43 (B). The average score of formative and daily tasks of the Management classroom A is 82 (A), and the average score of formative and daily tasks of the Management classroom B is 77,1 (B).